A pattern language for developing privacy enhancing technologies. (28th November 2011) - Hafiz, Munawar; Fayad, Mohamed E.; Singh, Shivanshu K.
SUMMARY A privacy enhancing technology (PET) is an application or a mechanism that allows users to protect the privacy of their personally identifiable information. Early PETs were about enabling anonymous mailing and anonymous browsing, but lately, there have been active research and development efforts in many other problem domains. This paper describes the first pattern language for developing PETs. Currently, it contains 12 patterns. These privacy patterns are not limited to a specific problem domain; they can be applied to design anonymity systems for various types of online communication, online data sharing, location monitoring, voting, and electronic cash management. The pattern language guides a developer when he or she is designing a PET for an existing problem or innovating a solution for a new problem. Copyright © 2011 John Wiley & Sons, Ltd.